A comprehensive review on optical and electrochemical aptasensor for detection of fumonisin B1 - Ma, Jiayu; Guo, Xiaodong (Frontiers in Nutrition, 2025)
Fumonisin B1 (FB1) contamination has emerged as a global concern due to its high incidence, severe toxicity, and profound implications for food safety and human health. Consequently, there is an urgent demand for the development of novel analytical techniques that enable simple, rapid, and accurate detection of FB1. Conventional methods for mycotoxin analysis, such as high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC–MS), thin-layer chromatography (TLC), gas chromatography–mass spectrometry (GC–MS), and enzyme-linked immunosorbent assay (ELISA), often suffer from limitations including high cost, time-consuming procedures, environmental sensitivity, and reliance on specialized expertise. Nucleic acid aptamers, generated via Systematic Evolution of Ligands by Exponential Enrichment (SELEX), have garnered significant attention as next-generation bioreceptors, demonstrating remarkable progress in food safety applications. Leveraging their high specificity and strong affinity for target molecules, aptamers have been successfully employed as alternatives to conventional methods for FB1 detection, leading to the development of diverse aptasensor platforms. This review systematically summarizes recent advancements (2013–2025) in optical and electrochemical aptasensors for FB1 detection, elucidating their working principles, merits, and limitations. It further evaluates the impact of material integration on sensor performance, identifies existing limitations in selected aptasensor configurations, and proposes corresponding optimization strategies. Finally, the current challenges hindering the practical implementation of aptasensors are critically analyzed, and future research directions are outlined to advance this promising field.